STUDI PERKEMBANGAN LEMBAGA KEMASYARAKATAN DALAM SISTEM PEMERINTAHAN DAERAH DI INDONESIA - Rauf, Rahyunir (UIR PRESS, 2016)
The rationale for this study due to the real role of civil society in assisting the government's villages, especially in the field of regional pemarintah government services, development, and social. Therefore, it is necessary to know the nature and history of the growth and development of the village community organizations to improve the understanding of the nature and purpose of the establishment of the village community in Indonesia. The results showed that social institutions kelurahandi Indonesia consists of Institutions Neighborhood, Pillars of Citizens, Community Development Institute, Institute for Community Development, Youth Organization, and other agencies that may be established by the community as needed. History of growth and development of each village community institutions are different from each other, but similar in purpose and role of helping the task of government, especially local government. The existence of social institutions that village was already long existed in Indonesia, some even since the reign of the population of Japan in Indonesia Recommendations research directed at the government, especially the local government to maintain the presence and synergy of civil society villages in assisting the government and local government, and expected to governments, especially local governments to be able to budget the cost of assistance to social institutions more proportional villages in the State Revenue and Expenditure in accordance with the activities and needs of community institutions.